Integrating Agriculture and Nutrition Actions to Improve Maternal and Child Nutrition: Research on Program Impact Pathways. - Webb, Patrick, 1959-; Kennedy, Eileen T., 1947-; Griffiths, Jeffrey K. (Tufts University. Tisch Library., 2016)
This report summarizes the discussions and outcomes of an LCIRAH (Leverhulme Center for Integrated Research on Agriculture and Health) workshop held June 21-22, 2012. Topics included the generation of research questions, challenges, and research opportunities.; Nutrition School: Technical Reports.; Keywords: Nutrition, Child health, maternal health, LCIRAH, Research opportunities, Research questions, 2014 Food and Nutrition Bulletin, 2012- NIL.